On the performance improvement of the optimal-sampling-inspired self-triggered control at implementation stage - Carlos Xavier Rosero Chandi (Maskay, 2017)
The self-triggered control includes a sampling strategy that focuses on decreasing the use of computational resources (processor and network) while preserving the same control performance as the one obtained via a controller with periodic sampling. Within this framework it has been developed recently a self-triggered control technique inspired by a sampling pattern whose optimal density minimizes the control cost, this approach is called “optimal-sampling inspired self-triggered control”. However, the strategies used to implement it on microprocessor-controlled systems working under perturbation are still unclear; this paper addresses some techniques to organize and improve the implementation on actual controllers. The proposed solution comprises both the formulation of two algorithms to organize the implementation and the insertion of a closed-loop observer to deal with the perturbation that normally appears on real plants. Regarding the former, certain computationally expensive processes involved in the implementation of this control technique are treated through their replacement by lightweight polynomials fitted at design stage. Simulations and practical experiments confirm the solution is effective and there could be an open research topic concerning observation in optimal-sampling self-triggered control strategies.